Extensive first-principles molecular dynamics study on Li encapsulation into C60 and its experimental confirmation. Issue 4 (8th January 2018) - Ohno, K.; Manjanath, A.; Kawazoe, Y.; Hatakeyama, R.; Misaizu, F.; Kwon, E.; Fukumura, H.; Ogasawara, H.; Yamada, Y.; Zhang, C.; Sumi, N.; Kamigaki, T.; et al.
Abstract : We propose a strategy to further increase the production ratio of Li + @C60 . Abstract : The aim of increasing the production ratio of endohedral C60 by impinging foreign atoms against C60 is a crucial matter of the science and technology employed towards industrialization of these functional building block materials. Among these endohedral fullerenes, Li + @C60 exhibits a wide variety of physical and chemical phenomena and has the potential to be applicable in areas spanning the medical field to photovoltaics. However, currently, Li + @C60 can be experimentally produced with only ∼1% ratio using the plasma shower method with a 30 eV kinetic energy provided to the impinging Li + ion. From extensive first-principles molecular dynamics simulations, it is found that the maximum production ratio of Li + @C60 per hit is increased to about 5.1% (5.3%) when a Li + ion impinges vertically on a six-membered ring of C60 with 30 eV (40 eV) kinetic energy, although many C60 molecules are damaged during this collision. On the contrary, when it impinges vertically on a six-membered ring with 10 eV kinetic energy, the production ratio remains at 1.3%, but the C60 molecules are not damaged at all. On the other hand, when the C60 is randomly oriented, the production ratio reduces to about 3.7 ± 0.5%, 3.3 ± 0.5%, and 0.2 ± 0.03% for 30 eV, 40 eV, and 10 eV kinetic energy, respectively. Based on these observations we demonstrate the possibility of increasing the production ratio by fixing six-membered rings atop C60 using the Cu(111) substrate or UV light irradiation. In order to assess the ideal experimental production ratio, the 7 Li solid NMR spectroscopy measurement is also performed for the multilayer randomly oriented C60 sample irradiated by Li + using the plasma shower method combined with inductively coupled plasma atomic emission spectroscopy (ICP-AES). Time-of-flight mass spectroscopy measurements are also performed to cross check whether Li + @C60 molecules are produced in the sample. The resulting experimental estimate, 4% for 30 eV incident kinetic energy, fully agrees with our simulation results mentioned above, suggesting the consistency and accuracy of our simulations and experiments.